2009
DOI: 10.1111/j.1755-0998.2009.02268.x
|View full text |Cite
|
Sign up to set email alerts
|

Variable microsatellite loci isolated from the Asian honeybee, Apis cerana (Hymenoptera; Apidae)

Abstract: We developed 12 polymorphic microsatellite loci for the Asian honeybee, Apis cerana using the magnetic particle method. Eight of these 12 were highly polymorphic, having four to seven alleles with an expected heterozygosity of 0.38 to 0.78. The primers also produce polymorphic products in related honeybee species such as Apis nigrocincta. These loci can be used to study parameters associated with genetic structure, such as paternity frequency and worker reproduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Loci were genotyped with primer pairs that were designed for A. mellifera (Solignac et al, 2007) and with some that were specifically designed for A. cerana (Takahashi et al, 2009). While the success rate of amplification was higher in the specific A. cerana primers, no significant differences existed between these two groups with regard to allele number, observed and expected heterozygosity, or the ratio of observed to expected heterozygosity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loci were genotyped with primer pairs that were designed for A. mellifera (Solignac et al, 2007) and with some that were specifically designed for A. cerana (Takahashi et al, 2009). While the success rate of amplification was higher in the specific A. cerana primers, no significant differences existed between these two groups with regard to allele number, observed and expected heterozygosity, or the ratio of observed to expected heterozygosity.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve microsatellite loci published for A. cerana (Takahashi et al, 2009) and 80 existing (Solignac et al,2007) or newly identified loci from the A. mellifera genome were screened in a subsample of eight individuals. Based on these screens, 18 primer combinations were selected that reliably amplified one specific, polymorphic microsatellite locus each (Table 1).…”
Section: Genotypingmentioning
confidence: 99%
“…All samples were genotyped at nine polymorphic microsatellite loci. Six of these loci were specific to Apis cerana (Takahashi et al, 2009) and three were specific to A. mellifera (Solignac et al, 2003). DNA was amplified using standard PCR conditions (Estoup et al, 1994) and genotypes were assigned as in Holmes et al (Holmes et al, 2010).…”
Section: Genetic Analysismentioning
confidence: 99%
“…For eggs, DNA was extracted from the entire egg in 50µL 5% Chelex solution. DNA from each individual was amplified at the following microsatellite loci: Ac1, Ac2, Ac3, Ac30 and Ac35 (Takahashi et al, 2009) in two polymerase chain reactions (multiplex 1: Ac1/Ac3/Ac35, multiplex 2: Ac2/Ac30) using standard PCR conditions (Estoup et al, 1994). Genotypes were scored as in Holmes et al (2010).…”
Section: Genotyping Of Samplesmentioning
confidence: 99%
“…All samples were genotyped at nine polymorphic microsatellite loci. Six of these loci were specific to Apis cerana (Takahashi et al, 2009) and three were specific to A. mellifera (Solignac et al, 2003). DNA was amplified using standard PCR conditions (Estoup et al, 1994) and genotypes were assigned as in Holmes et al (2010).…”
Section: Genetic Analysismentioning
confidence: 99%